Postura sentada de crianças com paralisia cerebral: influência da utilização do apoio de membros superiores - Périco, Bruna Carla [UNESP]; Carvalho, Sebastião Marcos Ribeiro de [UNESP]; Braccialli, Lígia Maria Presumido [UNESP] (My University, 2011)
Objective The purpose of this study was analyze the pressure distribution on the seat of the furniture and static balance in children with cerebral palsy in the sitting position without upper-limb support and resting the upper limbs on an adapted table. Methods A total of 12 children aged 4-11 years diagnosed with spastic cerebral palsy participated in this study. Data were collected with patient seated on a wheelchair adapted for two situations: 1) without upper-limb support, 2) with their arms resting on an adjusted table. Data were collected by the pressure sensor analysis software Conformat Research 5.8. Results The pressure peak was higher when the children were seated without limb support than with limbs resting on an adjusted table (p=0.015). The contact area distribution was smaller when the participants were seated without upper-limb support than with upper limbs resting on table (p=0.007). Conclusion The use of an adapted table to rest the upper limbs improved the pressure distribution on the seat of the furniture during the sitting posture of children with spastic cerebral palsy. There was no significant difference between static equilibrium without the table and with the upper limbs resting on an adjusted table.

Objetivo O estudo teve o propósito de analisar a distribuição de pressão no assento do mobiliário e o equilíbrio estático em crianças com paralisia cerebral na postura sentada sem apoio e com apoio dos membros superiores em mesa adaptada. Métodos Participaram deste estudo 12 crianças com diagnóstico de paralisia cerebral espástica, na faixa etária de 4 a 11 anos. A coleta de dados foi realizada com o participante sentado em cadeira adaptada em duas situações: 1) sem apoio dos membros superiores e 2) com os membros superiores apoiados em mesa adaptada. Os dados foram obtidos por meio do programa Conformat Research 5.8. Resultados O pico de pressão foi maior quando a amostra estudada permanecia sentada sem apoio dos membros superiores do que com apoio de membros superiores em mesa adaptada (p=0,015); houve menor distribuição da área de contato quando os participantes encontravam-se sentados sem apoio de membros superiores do que com apoio de membros superiores (p=0,007). Conclusão A utilização do apoio de membros superiores em mesa adaptada demonstrou melhora na distribuição de pressão no assento do mobiliário durante a postura sentada de crianças com paralisia cerebral espástica. Não houve diferença significativa entre o equilíbrio estático sem apoio e com apoio dos membros superiores em mesa adaptada.
Sitting posture of children with cerebral palsy: influence of upper-limb support
Keywords: paralisia cerebral; postura corporal; mobiliário